An ingenious invasive weed optimization (IWO) aided maximum power tracking for partially shaded photovoltaic array - Sridhar R; Boopathi C.S; Deepanjali Das; Sakshi Agrawal; Hardik Choubisa (Institute of Advanced Engineering and Science, 2019)
The inborn non-direct power voltage trademark bends concerning barometrical temperature and light makes the photovoltaic (PV) source a discontinuous one. Maximum power point (MPPT) following is a procedure through which most extreme accessible power is yielded from the PV for the given purpose of time. Prior, the customary MPPT methods, for example, perturb and observe, incremental conductance, hill climbing and so forth strategies were utilized and these methods stayed inadequate when the PV source is partially shaded (PS), since amid (PS) the power voltage (P-V) bends show different power crests. There wins each possibility that the ordinary calculations will stall out to the local maximum point and the global maximum point won't be accomplished and in this way control misfortune is brought about. The metaheuristic calculations give better arrangements however confront the downside of high weight on processor and enormous number of information prerequisites. In this way, in this paper, a novel calculation in light of invasive weed optimisation (IWO) technique is utilized to locate the Global maximum point for MPPT under in part shaded condition and it is contrasted and its nearby partner differential evolution(DE) MPPT algorithm and furthermore with the very much settled in perturb and observe (P&O) calculation. The proposed calculation is actualized in MATLAB condition and tried on a 3-board PV cluster arrangement of 150 W. The flexibility of the calculation is tried through various experiments and the outcomes demonstrate the effectiveness and exactness of the proposed calculation in finding the global maximum point.